2021
DOI: 10.4102/apsdpr.v9i1.482
|View full text |Cite
|
Sign up to set email alerts
|

The shortcomings of emergency remote teaching in rural settings of Zimbabwe during COVID-19 school closures: Lessons from China’s experience

Abstract: Background: In the wake of the coronavirus disease 2019 (COVID-19) pandemic, schools were forced to close indefinitely with no clue as to when they would reopen. Upon school closures, remote teaching was adopted, with online teaching becoming the most preferred mode of instruction, yet the Information Communication Technology (ICT) infrastructure was not adequate enough across the country.Aim: This article scrutinises the remote teaching approaches that were put in place in Zimbabwe in response to the closure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Other factors that make online learning less favorable especially in under resourced schools include poor internet connections, unaffordability of smart phones, lack of training on effective utilization of online learning platforms by both learners and teachers and complexity of conducting practical lessons online. These were echoed in research done by Adarkwah (2021), Almaiah et al (2020), Baticulon et al (2021), Dhawan (2020), Howard et al (2020), and Nhongo and Tshotsho (2021).…”
Section: Discussion Of the Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other factors that make online learning less favorable especially in under resourced schools include poor internet connections, unaffordability of smart phones, lack of training on effective utilization of online learning platforms by both learners and teachers and complexity of conducting practical lessons online. These were echoed in research done by Adarkwah (2021), Almaiah et al (2020), Baticulon et al (2021), Dhawan (2020), Howard et al (2020), and Nhongo and Tshotsho (2021).…”
Section: Discussion Of the Resultsmentioning
confidence: 96%
“…The argument is that, if pupils in areas with network and infrastructure for online teaching are failing, it implies rural schools can virtually not manage online teaching (Nhongo & Tshotsho, 2021). If urban school pupils are passing, then it is possible to conduct online teaching in Zimbabwe given the infrastructure for online learning.…”
Section: Open Accessmentioning
confidence: 99%
“…Governments, worldwide implemented school closures as a way of controlling the spread of COVID-19 in early 2020 (Burzynska & Contreras, 2020;Viner et al, 2020). History shows that the only time that Zimbabwe closed schools was from 1977 to 1980 as a result of the liberation struggle (Kriger, 1988;Nhongo & Tshotsho, 2021). It is vital to begin by looking at the experiences of other countries to understand how they adopted new approaches to ensure continuity in education during the COVID-19 induced lockdown.…”
Section: New Instructional Approaches During the Covid-19 Induced Sch...mentioning
confidence: 99%
“…While the South African government is promoting online learning as the only alternative in the context of COVID-19, this mode excludes many rural learners from teaching and learning, due to a lack of resources to connect to the internet, the learning management system, and low-tech software ( Dube, 2020 , p. 134). Nhongo and Tshotsho (2021) examined the approaches for teaching and learning that were used by Zimbabwe's schools during the COVID-19 lockdown. They suggested that a variety of approaches that suit particular physical environments should have been adopted for each geographical location instead of trying to use a uniform approach throughout the country.…”
Section: Online Teaching and Learningmentioning
confidence: 99%